HUBUNGAN PENGETAHUAN IBU, DUKUNGAN KELUARGA DAN ASUPAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Nova, Maria; Ilham, Dezi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Stunting is a chronic malnutrition problem as a result of lack of nutritional intake for a long time, so that it has an impact on the growth of children who have a height that is lower or shorter than the standard age. working area of the Water Children Health Center in 2021. This type of research is observational with a cross sectional design. The total population is 3,221 people, the research sample is 97 people using stratified random sampling technique. The data collected includes height with a digital height measuring device (digital wireless), Questionnaire, SQ FFQ. Data analysis using SPSS 20 using the Chi-Square test. The results of statistical tests showed stunting toddlers had low maternal knowledge 36.1%, less family support 36.1%, carbohydrate intake was less 74.2%, protein intake was less 59.8%, fat intake was 94.8%. The results of the bivariate analysis showed a significant relationship between the incidence of stunting and carbohydrate intake (P=0.019), protein intake (P=0.013), there was no significant relationship between the incidence of stunting and maternal knowledge (P=0.537), family support (P=1.00 ), fat intake (P=1.00). Mothers are expected to pay more attention to the food consumed by toddlers, not only providing foods that are liked by toddlers but also providing varied foods so that the nutritional needs of toddlers can be met. Keywords: Mother's knowledge, Family support, Macro intake